Marketing of apricot supplied to the market in Kandahar, Afghanistan - Hashimi, Sardar M.; Mohd Nawi, Nolila; Man, Norsida; Ahmadzai, Mohammad Khal (Universiti Putra Malaysia Press, 2020)
Horticulture crops considerably amplify the country’s profile. However, the quantity of apricot on the market has declined and its competitiveness has been challenged. This study focused on the marketing of apricot supplied to the market in Kandahar among 102 farmers. The respondents answered a structured questionnaire designed to explore the association between farmer’s socio-demographic factors and the quantity of apricot supplied to the market, to map the marketing channels used by the supply chain players, as well as to identify the marketing constraints. The results from the descriptive analysis showed that major actors in the study area were apricot farmers, wholesalers, collectors, retailers, and exporters. The results also revealed that the chain was constrained by the lack of storage, price setting, lack of governmental support, poor quality of apricot, lack of supply, high transportation cost, and lack of demand. Meanwhile, the results of the chi-square analysis revealed that farm size, education level, farming experience, and family size were significantly associated with the quantity of apricot supplied to the market except for farmer’s age. The findings of this study indicate that appropriate intervention mechanisms such as land acquisition schemes and education awareness programs are necessary for the expansion of farm size and farmers’ education to produce an increased quantity of apricot.